(untitled) (Al-Asalmiya Nursing: Jurnal Ilmu Keperawatan (Journal of Nursing Sciences), 2024)
PKU Muhammadiyah Hospital, Gamping, Sleman, D.I. Yogyakarta is a BPJS referral hospital which serves 700 patients a day. This requires managing drug supplies to avoid overstock or stockout incidents. To prevent this incident, the Pharmacy Installation of PKU Muhammadiyah Hospital, Gamping, Sleman, D.I. Yogyakarta applies the Minimum-Maximum Stock Level (MMSL) inventory control method. The aim of this research is to determine the effect of applying the MMSL method on the inventory value of Pareto A generik medicines in the outpatient pharmacy unit of PKU Muhamadiyah Gamping Hospital, Sleman, D.I. Yogyakarta. This research is quasi-experimental research with a non-equivalent without control design. The population and sample in this study were generik drugs in the road unit of PKU Muhamadiyah Gamping Hospital, Sleman, D.I. Yogyakarta. The inclusion criteria in this study were generic drugs with Paretto category A. The exclusion criteria were drugs with unstable supply. The number of samples collected in this study was 23 generik drugs selected using a purposive sampling technique. The intervention was carried out by applying the MMSL method to the stock of 23 generic drugs. The application of the MMSL method to drug stocks starts from April - May 2020. The effect of applying the MMSL method on investment value was analyzed using the Wilcoxon test. The results of the research show that there is an influence of the application of the MMSL method on the inventory value of Paretto A generik drugs in the outpatient pharmacy unit of PKU Muhammadiyah Gamping Hospital, Yogyakarta. Analysis of the MMSL intervention showed a significance of p= 0.000. The value of drug inventory before the intervention was IDR 15,175,340.00, while the inventory value after the intervention was reduced to IDR 11,864,748.00. This shows an inventory efficiency of IDR 3,310,592.00